Holes : Holes #1 - Sachar, Louis (New York : Farrar, 1998)
As further evidence of his family's bad fortune which they attribute to a curse on a distant relative, Stanley Yelnats is sent to a hellish correctional camp in the Texas desert where he finds his firs
7-A.
12-A.
7.
Awarded the Newbery Medal, 1999.
Keywords: Juvenile delinquency -- Fiction; Homeless persons -- Fiction; Buried treasure -- Fiction